Процена 99Тцм-ДТПА орбите СПЕЦТ/ЦТ у комбинацији са тестом функције штитне жлезде у лечењу радиоактивног јода И-131 код пацијената са офталмопатијом-хипертиреозом повезаном са штитном жлездом - Su, Li; Mi, Ping; Niu, Wenqiang; Zhou, Ting; Yang, Wang; Chen, Cheng; Huang, Chenggang (Journal of Medical Biochemistry, 2024)
Objective: Thyroid-associated ophthalmopathy (TAO) is an autoimmune response to inflammation of the thyroid and orbital tissue. This research evaluated the efficacy of 99Tcm-DTPA orbital SPECT/CT combined with thyroid function test in radioactive iodine I-131 (RAI) treatment of TAO-hyperthyroidism. Methods: We retrospectively studied clinical activity score (CAS), blood thyrotropine (TSH), free triiodothyronine (FT3), free thyroxine (FT4), thickness of extra-ocular muscle (EOM), and uptake rate (UR) of 99Tcm-DTPA orbital SPECT/CT of 43 patients after 6 months of treatment with 20 mCi RAI. Parameters were compared before and after RAI in patients assessed as effectively treated (normal thyroid function or hypothyroidism), and correlations between blood FSH, FT3, FT4, thickness of EOM, and UR were analyzed after treatment. Results: After RAI, 35 cases (77 eyes, 81.4%) had normal or hypothyroidism and 8 cases (16 eyes, 12.0%) had hyperthyroidism. Compared with the patients who failed treatment, effectively treated patients had lower CAS, FT3, FT4, and UR and higher blood TSH. In patients with effective treatment, UR of the inferior rectus muscle was positively correlated with FT3 and FT4. Adverse RAI outcomes were associated with smoking and higher iodine-thyroid iodine uptake before treatment. Conclusions: Combined with TSH, FT3, and FT4 levels, the reduction of 99Tcm-DTPA orbital SPECT/CT UR also indicates an improvement in the disease course of patients. The UR of inferior rectus muscle can be an objective index to evaluate the curative effect of TAO patients.